2019
DOI: 10.1200/jco.2019.37.15_suppl.522
|View full text |Cite
|
Sign up to set email alerts
|

Do all patients with HER2-positive breast cancer require one year of adjuvant trastuzumab?: A systematic review and meta-analysis.

Abstract: 522 Background: One year of adjuvant trastuzumab (T) remains the standard treatment for patients with HER2 positive breast cancer. Results from randomized trials with diverse non-inferiority margins comparing one year to a shorter duration of adjuvant T were not consistent, particularly with the PERSEPHONE and the final PHARE and Short-HER trials’ results. Our objective was to conduct a systematic review and meta-analysis of randomized trials in patients with HER2 positive breast cancer to assess whether a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Admittedly, our meta-analysis is not the first to compare short durations vs. 12 months of trastuzumab, and there are at least six similar meta-analyses or systematic reviews so far (26,27,(36)(37)(38)(39). However, these similar studies were found to have some serious limitations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Admittedly, our meta-analysis is not the first to compare short durations vs. 12 months of trastuzumab, and there are at least six similar meta-analyses or systematic reviews so far (26,27,(36)(37)(38)(39). However, these similar studies were found to have some serious limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, the two studies presented at ASCO 2019 provided only brief abstracts rather than detailed full-text articles, and they may lack some important information (36,37). Secondly, most similar studies compared short durations vs. 12 months of trastuzumab, but we concentrated on 6 months of trastuzumab rather than several different short durations (26,27,(36)(37)(38)(39). There may be substantial bias if 6 months and other different short durations are combined arbitrarily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations